Clinical implications of immune checkpoint markers and immune infiltrates in patients with thymic neuroendocrine neoplasms - Liu, Man; Hu, Wanming; Zhang, Yixuan; Zhang, Ning; Chen, Luohai; Lin, Yuan; Wang, Yu; Luo, Yanji; Guo, Yu; Chen, Minhu; Chen, Jie (Frontiers in Oncology, 2022)
The potential response of immune checkpoint blockade (ICB) in thymic neuroendocrine neoplasms (T-NEN) is largely unknown and full of great expectations. The expression of immune checkpoint molecules and immune infiltrates greatly determine the response to ICB. However, studies regarding the immune landscape in T-NEN are scarce. This work was aimed to characterize the immune landscape and its association with clinical characteristics in T-NEN. The expression of programmed cell death protein 1 (PD-1) and its ligand, programmed death ligand-1 (PD-L1), and the density of tumor-infiltrating lymphocytes (TILs), monocytes, and granulocytes were determined by immunohistochemical (IHC) staining on tumor tissues from T-NEN. Immune landscapes were delineated and correlated with clinicopathological factors. We found that T-NEN with increased immune cell infiltration and enhanced expression of PD-1/PD-L1 tended to have restricted tumor size and less metastases. A higher density of CD8+ TILs was associated with a significantly lower rate of bone metastasis. The clinical application of ICB elicited durable partial responses with satisfactory safety in two patients with T-NEN. This innovative study delineated for the first time the heterogeneous immune landscape in T-NEN and identified CD8+ TILs as a potential marker to predict bone metastasis. An “immune-inflamed” landscape with the presence of TILs predominated in T-NEN, making T-NEN a potentially favorable target for ICB treatment. Further judicious designs of “tailor-made” clinical trials of ICB in T-NEN are urgently needed.